Peran Platform Merdeka Mengajar (PPM) dalam Meningkatkan Efektivitas Implementasi Kurikulum Merdeka - Elpin, Agus; Simarona, Nuri; Aunurrahman, Aunurrahman; Halida, Halida (STAI Auliaurrasyidin Tembilahan, 2024)
Merdeka Mengajar Platform (PMM) stands as a government initiative to bolster the understanding and implementation of the Merdeka Curriculum. This research aims to assess the extent to which PMM contributes positively to supporting the comprehension of concepts and the implementation of the Merdeka Curriculum. Employing a mixed methods research design encompassing both quantitative and qualitative approaches, data collection involved surveys and in-depth interviews. Descriptive and thematic analyses were conducted to interpret the data. The findings indicate the effectiveness of PMM in supporting the understanding of the Merdeka Curriculum. This is evident through the high satisfaction of respondents with PMM, particularly regarding the provision of comprehensive information and references, interactive features, and the ability to customize materials. Recommendations for PMM development include enhancing material quality, incorporating innovative features, and improving accessibility for users with special needs or in remote areas. This research contributes valuable insights for the ongoing enhancement of PMM, making it a more robust tool in facilitating understanding and implementation of the Merdeka Curriculum.